2013
DOI: 10.1186/2051-5960-1-35
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a neuronal transcription factor network involved in medulloblastoma development

Abstract: BackgroundMedulloblastomas, the most frequent malignant brain tumours affecting children, comprise at least 4 distinct clinicogenetic subgroups. Aberrant sonic hedgehog (SHH) signalling is observed in approximately 25% of tumours and defines one subgroup. Although alterations in SHH pathway genes (e.g. PTCH1, SUFU) are observed in many of these tumours, high throughput genomic analyses have identified few other recurring mutations. Here, we have mutagenised the Ptch+/- murine tumour model using the Sleeping Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 67 publications
(190 reference statements)
1
30
0
Order By: Relevance
“…Interestingly, nearly 40% of genes identified in our screen were associated with transcription, consistent with a previous screen for medulloblastoma disease genes (49). Transcription factors play essential roles in coordinated gene expression during development.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, nearly 40% of genes identified in our screen were associated with transcription, consistent with a previous screen for medulloblastoma disease genes (49). Transcription factors play essential roles in coordinated gene expression during development.…”
Section: Discussionsupporting
confidence: 72%
“…For example, if NFIs drive differentiation during development, then it is a strong possibility that inactivating mutations in Nfi genes will be identified in developmental based cancers. Indeed, as discussed in this review, there are a number of recent studies that have shown a potential role for inactivating mutations in NFIs in contributing to medulloblastoma, the most common childhood brain cancer (Wu et al, 2012; Genovesi et al, 2013; Lastowska et al, 2013). It might therefore be interesting to determine whether NFIs act as oncogenes in adult-derived cancers, particularly as these cancers are thought to be caused by deregulated or chronic repair mechanisms, whereby stem cells are recruited to repopulate tissues.…”
Section: Nfis In Adult Stem Cell Niches: a Putative Function In Cell-mentioning
confidence: 98%
“…Medulloblastoma is a common malignant brain tumour of childhood, and certain subtypes of this disease have long been known to arise from GNPs of the EGL (Marino et al, 2000; Oliver et al, 2005; Schuller et al, 2008). Recently, a number of studies have identified NFI factors as being involved in medulloblastoma tumorigenesis, with transposon-mediated inactivation of Nfia, Nfib and/or Nfix shown to accelerate medulloblastoma initiation and/or progression in mouse models of medulloblastoma derived from GNPs (Wu et al, 2012; Genovesi et al, 2013; Lastowska et al, 2013). Indeed, a role for Nfia in medulloblastoma formation in vivo was recently supported by data showing that combined haploinsufficiency for both Nfia and Ptch1 exacerbated tumour development compared to the Ptch1 haploinsufficiency alone (Genovesi et al, 2013).…”
Section: Nfis Drive Stem and Progenitor Cell Differentiation During Dmentioning
confidence: 99%
“…Indeed, as discussed in this review, there are a number of recent studies that have shown a potential role for inactivating mutations in NFIs in driving tumorigenesis in medulloblastoma, the most common childhood brain cancer (Wu et al, 2012;Genovesi et al, 2013;Lastowska et al, 2013). It might therefore be interesting to determine whether NFIs act as oncogenes in adult-derived cancers, particularly as these cancers are thought to be caused by deregulated or chronic repair mechanisms, whereby stem cells are recruited to repopulate tissues.…”
Section: Nfix Promotes Survival Of Hematopoietic Stem and Progenitor mentioning
confidence: 98%
“…Medulloblastoma is a common malignant brain tumour of childhood, and certain subtypes of this disease have long been known to arise from GNPs of the EGL (Marino et al, 2000;Oliver et al, 2005;Schuller et al, 2008). Recently, a number of studies identified NFI factors as potential drivers of medulloblastoma tumorigenesis, with transposonmediated inactivation of Nfia, Nfib and/or Nfix shown to accelerate medulloblastoma initiation and/or progression in a mouse model of medulloblastoma derived from GNPs (Wu et al, 2012;Genovesi et al, 2013;Lastowska et al, 2013). Nfia was subsequently confirmed as a specific driver of medulloblastoma in vivo, with combined haploinsufficiency for both Nfia and Ptch1 exacerbating tumour development compared to the Ptch1 haploinsufficiency alone (Genovesi et al, 2013).…”
Section: Nfis Are Potential Drivers Of Medulloblastoma Tumorigenesismentioning
confidence: 99%